A prospective, randomized, placebo‐controlled, double‐blind trial about safety and efficacy of combined treatment with alteplase (rt‐PA) and Cerebrolysin in acute ischaemic hemispheric stroke. Issue 2 (26th September 2012) - Lang, Wilfried; Stadler, Christian H.; Poljakovic, Zdravka; Fleet, David; ,; Willeit, Johann; Brainin, Michael; Gruber, Franz; Demarin, Vida; Antoncic, Igor; Lusic, Ivo; Bar, Michal; et al.
<x xml:space="preserve">Abstract</x> Background The neurotrophic drug Cerebrolysin accelerated recovery and prevented acute neuronal damage in preclinical models of ischaemia. Previous clinical trials support therapeutic effects in stroke patients. The study investigated whether the combination with alteplase and Cerebrolysin is safe and can further reduce disability after acute ischaemic stroke. Methods This placebo‐controlled, double‐blind trial involved 119 patients with acute ischaemic hemispheric stroke, randomly assigned to a combined treatment with alteplase plus Cerebrolysin or placebo (administered 1 h after thrombolytic treatment) starting within three‐hours after onset of symptoms. A daily i.v. infusion of 30 ml Cerebrolysin or placebo was given for 10 consecutive days. Primary outcome was the modified Rankin Scale at day 90. A sequential design with interim analyses was applied. Results The third interim analysis did not show a benefit in the modified Rankin Scale for Cerebrolysin on day 90 compared to placebo and the study was stopped. The National Institutes of Health Stroke Scale responder analysis (secondary outcome measure) showed significantly more patients with an improvement of 6 or more points (or a total score of 0 or 1) after two‐, five‐, 10, and 30 days in the Cerebrolysin group. Similar trends were observed for the modified Rankin Scale responder analysis without achieving statistical significance. There was no difference between treatment groups regarding adverse events. Conclusions The combination of Cerebrolysin with recombinant tissue‐Plasminogen Activator is safe for treatment of acute ischaemic stroke but did not improve outcome at day 90. During the treatment period with Cerebrolysin (10 days), significantly more patients had a favourable response in neurological outcome measures (National Institutes of Health Stroke Scale) as compared to the placebo group.